Identification of Aph1, a Phosphate-Regulated, Secreted, and Vacuolar Acid Phosphatase in Cryptococcus neoformans - Sophie Lev (American Society for Microbiology, 2014)
ABSTRACT Cryptococcus neoformans strains isolated from patients with AIDS secrete acid phosphatase, but the identity and role of the enzyme(s) responsible have not been elucidated. By combining a one-dimensional electrophoresis step with mass spectrometry, a canonically secreted acid phosphatase, CNAG_02944 (Aph1), was identified in the secretome of the highly virulent serotype A strain H99. We created an APH1 deletion mutant (Δaph1) and showed that Δaph1-infected Galleria mellonella and mice survived longer than those infected with the wild type (WT), demonstrating that Aph1 contributes to cryptococcal virulence. Phosphate starvation induced APH1 expression and secretion of catalytically active acid phosphatase in the WT, but not in the Δaph1 mutant, indicating that Aph1 is the major extracellular acid phosphatase in C. neoformans and that it is phosphate repressible. DsRed-tagged Aph1 was transported to the fungal cell periphery and vacuoles via endosome-like structures and was enriched in bud necks. A similar pattern of Aph1 localization was observed in cryptococci cocultured with THP-1 monocytes, suggesting that Aph1 is produced during host infection. In contrast to Aph1, but consistent with our previous biochemical data, green fluorescent protein (GFP)-tagged phospholipase B1 (Plb1) was predominantly localized at the cell periphery, with no evidence of endosome-mediated export. Despite use of different intracellular transport routes by Plb1 and Aph1, secretion of both proteins was compromised in a Δsec14-1 mutant. Secretions from the WT, but not from Δaph1, hydrolyzed a range of physiological substrates, including phosphotyrosine, glucose-1-phosphate, β-glycerol phosphate, AMP, and mannose-6-phosphate, suggesting that the role of Aph1 is to recycle phosphate from macromolecules in cryptococcal vacuoles and to scavenge phosphate from the extracellular environment. IMPORTANCE Infections with the AIDS-related fungal pathogen Cryptococcus neoformans cause more than 600,000 deaths per year worldwide. Strains of Cryptococcus neoformans isolated from patients with AIDS secrete acid phosphatase; however, the identity and role of the enzyme(s) are unknown. We have analyzed the secretome of the highly virulent serotype A strain H99 and identified Aph1, a canonically secreted acid phosphatase. By creating an APH1 deletion mutant and an Aph1-DsRed-expressing strain, we demonstrate that Aph1 is the major extracellular and vacuolar acid phosphatase in C. neoformans and that it is phosphate repressible. Furthermore, we show that Aph1 is produced in cryptococci during coculture with THP-1 monocytes and contributes to fungal virulence in Galleria mellonella and mouse models of cryptococcosis. Our findings suggest that Aph1 is secreted to the environment to scavenge phosphate from a wide range of physiological substrates and is targeted to vacuoles to recycle phosphate from the expendable macromolecules.